Molecular epidemiology and antimicrobial resistance mechanisms of Campylobacter coli from diarrhoeal patients and broiler carcasses in Belgium. Issue 1 (12th November 2018) - Elhadidy, Mohamed; Miller, William G.; Arguello, Hector; Álvarez‐Ordóñez, Avelino; Dierick, Katelijne; Botteldoorn, Nadine
Abstract: The aim of this study was to better understand the molecular epidemiology of Campylobacter coli isolated from multiple sources in Belgium, by studying the genotypic diversity and antimicrobial resistance phenotypes and resistance mechanisms of 59 C. coli isolates. Isolates from broiler carcasses and human cases were genotyped using multilocus sequence typing (MLST), porA typing, flagellin gene A restriction fragment length polymorphism ( flaA –RFLP) typing, and by PCR binary typing (P‐BIT). Thirty‐two MLST sequence types, 24 flaA types, 31 porA alleles, and 29 P‐BIT types were identified among the screened isolates. Some types and alleles were shared among strains recovered from both broiler carcasses and diarrhoeal patients. Both porA typing and MLST revealed a similar discriminatory power (0.969), which was the highest discriminatory power when compared to other methods. Minimum inhibitory concentrations against seven different antibiotics (ciprofloxacin, chloramphenicol, nalidixic acid, streptomycin, tetracycline, gentamicin, and erythromycin) were analysed. Strains were most frequently resistant to tetracycline (81.4%), followed by: ciprofloxacin and nalidixic acid (76.3%); streptomycin (33.9%); erythromycin (27.1%); and chloramphenicol (3.4%). All isolates were sensitive to gentamicin. Multidrug resistance was observed in 24 of 59 C. coli isolates (40.7%). Molecular screening of antimicrobial resistance mechanisms revealed the predominance of the gyrA T86I substitution among ciprofloxacin‐ and nalidixic acid‐resistant isolates, the tet(O) gene among tetracycline‐resistant isolates and the 23S rRNA A2075G mutation among erythromycin‐ resistant isolates. Furthermore, some erythromycin‐resistant isolates harboured a diverse array of resistance mechanisms, including the presence of ermB, 23S rRNA A2074G mutation, and point mutations the rplD and rplV ribosomal genes, and the cmeABC multidrug efflux pump genes.